Unplasticized poly(vinyl chloride) (PVC-U) profiles for the fabrication of windows and doors. Classification, requirements and test methods. Non-coated PVC-U profiles with light coloured surfaces Part 1, (4th September 2020) - British Standards Institution,
No abstract available